The genus Mimesa in China with descriptions of two new species (Hymenoptera: Apoidea: Crabronidae) - Ma, Li; Li, Qiang; Chen, Xue-Xin (Zootaxa, 2008)
The genus Mimesa Shuckard (Crabronidae: Pemphredoninae: Psenini) from China is reviewed and a key to the Chinese species is provided. Two new species, M. infossa Ma, Li and Chen, sp. nov. from Tibet, China and M. rhyssocephalica Ma, Li and Chen, sp. nov. from Yunnan, China are described and illustrated. Five species are reported from China for the first time: Mimesa breviventris F. Morawitz, M. caucasica Maidl, M. crassipes A. Costa, M. sibirica (de Beaumont), and M. grandii Maidl. In addition, the unknown females of M. filippovi (Gussakovskij) and M. kaszabi (Tsuneki) are described.